Geographic factors of formation of Kazakhstan arid relief - Akpambetova, K.M.; David, L.; Chistov, А.А. (Fundamental and Experimental Biology, 2016)
In the article geographic factors of influence on the arid relief of Kazakhstan were considered. Changing of pluvial and xerothermic ages is shown. Conformity of xerothermic epoch with tendencies of modern relief-forming is defined. Arid type of climate of Kazakhstan contributes to the lack of local flowing waters. It is known that, climatic, hydrographic and geomorphologic factors influence on the distribution and accumulation of groundwaters.